Institutional differences across resource-based economies - Utku Teksoz; Katerina Kalcheva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
To predict economic success and failure, academics and policymakers alike are interested in the differences in institutional structures across natural resource-based economies. This paper uses a political economy framework to examine the effect of institutional variables on per capita Gross-Domestic-Product in resource-rich economies. After controlling for institutions, natural resource rents cease to have a negative impact on long-term growth. Institutions in resource-based economies foster economic growth when voice and accountability are in place; broad-based rule of law is enforced with secure property rights, and control of corruption; and when government effectiveness, regulatory quality, and political stability are positively perceived.
Keywords: H1; O10; O30; O40; P16; Q33; 330; institutions; growth; political power; rents; property rights; resource-based economies